Results of Therapy Including Omalizumab in Adolescents With Recurrent Urticaria: Retrospective Cohort Study - Vera G. Kalugina; Elena A. Vishneva; Leyla S. Namazova-Baranova; Polina R. Grinchik (Педиатрическая фармакология, 2019)
Relevance. Omalizumab is recommended for treatment of severe forms of recurrent urticaria in children since 12 years old. Though the Omalizumab efficiency and safety in children with recurrent urticaria have not been studied specifically.Objective. To estimate results of the therapy including Omalizumab in adolescents with recurrent urticaria.Methods. We have studied clinical records of day hospital patients aged from 12 to 17 with recurrent urticaria uncontrolled with second-generation antihistamines and/or immunosuppressive drugs at least for a month (in standard or higher dose), but receiving Omalizumab (300 mg once in 4 weeks subcutaneously). The main result of this therapy is disease control (urticaria activity score over 7 days, UAS7, equal to zero) at 3 and 6 months of therapy. Additional outcomes of therapy: number of significant recrudescence (use of glucocorticosteroids or emergency hospitalization) at 6th month of therapy and in 6 and 12 months after its end; end of concomitant treatment (antihistamines and/or immunosuppressive drugs) at 3 and 6 months and genetically engineered biological agent (GEBD); remission (UAS7 = 0) after 6 and 12 months after GEBD cessation; adverse effects of Omalizumab therapy (any medical cases connected with GEBD).Results. The disease control at 3 months of treatment was reached in 12 (67%) patients out of 18 children with recurrent urticaria, at 6 months — at 13 (72%) patients. During Omalizumab therapy and at 6 months after therapy cessation there were no significant recrudescence, at 12 months after therapy cessation — at 1 (6%) adolescent. The concomitant treatment was ended after 3 months at 3 (17%) patients, after 6 months — at 10 (56%) patients. Remission was sustained at 11 (61%) out of 18 patients at 6 months and at 9 (60%) out of 15 patients at 12 months after the therapy end. Adverse effects of Omalizumab have not been noted.Conclusion. Addition of Omalizumab to the therapy in adolescents with uncontrolled recurrent urticaria let us reach remission of disease in most cases by 6 months of treatment.